Effects of Magnesium Deficiency on the Photosynthesis and Respiration of Leaves of Sugar Beet - Terry, Norman (1974)
The effects of Mg deficiency on the photosynthesis and respiration of sugar beets (Beta vulgaris L. cv. F58-554H1) were studied by withholding Mg from the culture solution and by following changes in CO(2) and water vapor exchange of attached leaves. Leaf blade Mg concentration decreased from about 1200 to less than 200 meq kg(−1) dry matter without change in the rate of photosynthetic CO(2) uptake per unit leaf area, while from 200 to 50 meq kg(−1) the rate decreased to one-third. Rates of photorespiratory evolution of CO(2) into CO(2)-free air responded to Mg like those of photosynthetic CO(2) uptake, the rates decreasing to one-half, below 200 meq kg(−1). Respiratory CO(2) evolution in the dark increased almost 2-fold in low Mg leaves. Magnesium deficiency had less effect on leaf (mainly stomatal) diffusion resistance (r(1)) than on mesophyll resistance (r(m)); in Mg-deficient plants r(m) increased from 2.9 to 7.1 sec cm(−1), whereas r(1) became significantly greater than the control value only in the most severe instances of Mg deficiency.